ANALISIS BUKU SISWA MATEMATIKA KURIKULUM 2013 UNTUK SEKOLAH MENENGAH PERTAMA (SMP) KELAS VII BERDASARKAN RUMUSAN KURIKULUM 2013 - Masruri, Muslih; Sunardi, Sunardi; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2016)
Curriculum is one of the essential requirements in the administration of education system. In the academic year 2013/2014, Indonesian government through the Ministry of Education implement a new curriculum called 2013 curriculum. For the successful implementation of 2013 curriculum, the government published a student book as an effort of supporting in learning activities. Analysis on the student book is needed for reviewing the suitability of student book by 2013 curriculum formulation. The analysis is based on four criteria consisting of competence, materials of math, learning approaches and assessment of learning. Research carried out by using the method of documentation and questionnaires. The results showed that the suitability of the student book with competence in the curriculum is 86.97% (very suitable), the materials of math is 87.27% (very suitable), the learning approaches is 87.50% (very suitable), and the suitability with the assessment of learning is 69.10% (suitable). Based on the research that has been done, the lowest number of suitability is the aspect of authentic assessment. Therefore, adding more tasks and activities that reflecting the authentic assessment in the student book such as portfolio and practice test would be highly recommended